Diagnostic value of paraclinical markers in the early diagnosis of various forms of acute pancreatitis - Dzyubanovsky, Igor; Banadyga, Andriy; Banadyha, Nataliya (Journal of Education, Health and Sport, 2016)
Dzyubanovsky I. Ya., Banadyga A. I., Banadyha N. V. Diagnostic value of paraclinical markers in the early diagnosis of various forms of acute pancreatitis. Journal of Education, Health and Sport. 2016;6(4):63-70. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49830 http://ojs.ukw.edu.pl/index.php/johs/article/view/3451 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 10.04.2016. Accepted: 10.04.2016. Diagnostic value of paraclinical markers in the early diagnosis of various forms of acute pancreatitis I. Ya. Dzyubanovsky, A. I. Banadyga, N. V. Banadyha Department of Surgery of Education-Research Institute of Postgraduate training of the I. Ya. Horbachevsky Ternopil State Medical University, Ternopil, Ukraine Abstract The comparative analysis of the diagnostic value of laboratory and instrumental methods of diagnosis in patients with acute pancreatitis (AP) was made for early diagnosis and prediction of infected acute necrotizing pancreatitis (ANP). The results were compared with other laboratory parameters, sonography and computer tomography (CT) of the abdomen with mild and severe pancreatitis. Laboratory examination methods were carried out in dynamics during the first week of illness, as well as instrumental. Objective: to increase the effectiveness of treatment of patients with infected ANP by improving methods of early diagnosis. Materials and methods. The study was conducted at the Ternopil University Hospital in a period from 2014 year to 2015 and based on the assessment of the severity of AP in 37 patients. The results of investigation. Among examined with a moderate AP were-17(45.94%), severe-14 (37.84%), critical- 6 (16.22%) patients. Medium age of patients was 43,4 ± 1,44 in the first study group and 48,60 ± 1,57 - in the second group. Of all the 35 analyzed biochemical laboratory parameters allocated 7 (amylase, diastase, ALT, AST, bilirubin, protein, glucose), with a probable difference (P <0.05). In the analysis of blood procalcitonin was found that in 14 patients (70%) of II group (severe and critical AP) the levels of marker were increased (> 2,0 ng / ml). II group had subgroup of 5 patients (25%- operated early) who had the level of marker: 7,32+-3,0ng/ml, p<0,05 and septic inflammation was evidenced in operating room.Ultrasonography at admission to hospital in patients of I group found changes in the pancreas that were characteristics of AP in 15 patients (88%). High diagnostic value of CT in patients with critical AP was in 83,33% (3patients), with severe - in 88.88%(8 patients). Among amylase and diastase on the first day of illness correlations were: r=0,75 in I group and r=0,73 in ІІ. On the third day: r=0,76 and r=0,78 in I and II groups. Conclusions. After analyzing the data, we found that in determining the level of procalcitonin, amylase, blood glucose, and urine diastase in comparison with clinical parameters at admission AP diagnosis was confirmed in 17 (85.0%) and 15 (88.23%) cases in I and II groups. Key words: acute pancreatitis, infected pancreatic necrosis, procalcitonin, diagnosis.